The practical importance of linguistics - Bahriddinova , Kumush; Rakhimova , Saida (WORLD INTERNATIONAL CONFERENCE ON SCIENCE, TECHNOLOGY AND EDUCATION, 2026)
This article discusses the practical significance of linguistics, its role in society, and its application in various fields. Linguistics not only studies the structure of language but also serves as an essential tool in education, translation, communication, information technology, and intercultural relations. The article also analyzes its role in developing speech culture and establishing language norms.